2008
DOI: 10.1071/pc080215
|View full text |Cite
|
Sign up to set email alerts
|

Feeding Flipper: a case study of a humandolphin interaction

Abstract: We document a human-dolphin interaction involving the illegal feeding of wild Bottlenose Dolphins (Tursiops sp.) in Cockburn Sound, Western Australia from 1993-2003. In 1993 only one dolphin was considered conditioned to human interaction through food reinforcement. By 2001, 16% (n = 12) of the resident community of 74 adult dolphins were conditioned, and at least 14 dolphins were conditioned by 2003. Of the 13 conditioned dolphins of known sex, 11 (85%) were males. We observed conditioned dolphins initiating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
65
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(66 citation statements)
references
References 0 publications
0
65
1
Order By: Relevance
“…Second, the rough-toothed dolphins moved from boat to boat and followed close to the stern of boats for prolonged periods. Similar behaviour has been observed in conditioned (in this case, to deliberate feeding by humans) bottlenose dolphins in Australia, which moved methodically from boat to boat in expectation of food (Finn et al, 2008). Additionally, rough-toothed dolphins pursued the lures in toward the vessel sterns as the lines were retrieved.…”
mentioning
confidence: 55%
See 2 more Smart Citations
“…Second, the rough-toothed dolphins moved from boat to boat and followed close to the stern of boats for prolonged periods. Similar behaviour has been observed in conditioned (in this case, to deliberate feeding by humans) bottlenose dolphins in Australia, which moved methodically from boat to boat in expectation of food (Finn et al, 2008). Additionally, rough-toothed dolphins pursued the lures in toward the vessel sterns as the lines were retrieved.…”
mentioning
confidence: 55%
“…For example, in Western Australia, the number of wild bottlenose dolphins conditioned to illegal feeding by recreational fishing boats increased from one animal in 1993 to at least 14 by 2003 (Finn et al, 2008). The rapid increase in depredation behaviour by several killer and sperm whale populations worldwide is considered to be an example of cultural transmission (Whitehead et al, 2004), and fishermen have observed bottlenose dolphins teaching depredation behaviour to their calves in the Florida king mackerel troll fishery (Zollett & Read, 2006).…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Only a small number of studies have investigated the impact of provisioning (feeding) wild dolphins (Finn, Donaldson, & Calver, 2008;Powell & Wells, 2011;Samuels & Bejder, 2004), despite the prevalence of these interactions. In 1988, commercial dolphin feeding programs were initiated north of Savannah, Georgia and banned in 1993, as the activity was deemed to violate the US Marine Mammal Protection Act (MMPA).…”
Section: Food-provisioning Tourism and Cetaceansmentioning
confidence: 98%
“…The take of marine mammals, including harassment and feeding, is illegal under the U.S. Marine Mammal Protection Act of 1972 (MMPA), and concern is growing over human-dolphin interactions concentrated in certain coastal areas in the Gulf of Mexico where injuries or fatalities to bottlenose dolphins, specifically, have been documented. These encounters, which bear great potential and risk for injury to the public and to individual dolphins and populations, may take the form of interaction with recreational or commercial fishing vessels and gear (Wells et al, 1998;Powell and Wells, 2011), direct interaction with humans through feeding or swim-with activities (Colborn, 1999;Samuels and Bejder, 2004;Danil et al, 2005;Cunningham-Smith et al, 2006;Finn et al, 2008;Perrtree et al, 2014), or encounters with vessels during whale or dolphin viewing activities (Wells and Scott, 1997;Nowacek et al, 2001;Constantine et al, 2004;Goodwin and Cotton, 2004;Lusseau, 2006;Timmel et al, 2008). Impacts to wild dolphins from these activities include conditioning and alteration of normal foraging and resting behaviors; disturbance and ultimate dispersal of populations from preferred habitat; injury from vessel strikes or directed harm, and reduced reproductive success, all of which can threaten survival.…”
mentioning
confidence: 99%